Small RNA ArcZ Regulates Oxidative Stress Response Genes and Regulons in Erwinia amylovora - Schachterle, Jeffrey K.; Onsay, Daphne M.; Sundin, George W. (Frontiers in Microbiology, 2019)
Erwinia amylovora, causative agent of fire blight disease of apple and pear trees, has evolved to use small RNAs for post-transcriptional regulation of virulence traits important for disease development. The sRNA ArcZ regulates several virulence traits, and to better understand its roles, we conducted a transcriptomic comparison of wild-type and ∆arcZ mutant E. amylovora. We found that ArcZ regulates multiple cellular processes including enzymes involved in mitigating the threat of reactive oxygen species, and that the ∆arcZ mutant has reduced catalase activity and is more susceptible to exogenous hydrogen peroxide. We quantified hydrogen peroxide production by apple leaves inoculated with E. amylovora and found that the while wild-type E. amylovora cells produce enough catalase to cope with defense peroxide, the ∆arcZ mutant is likely limited in virulence because of inability to cope with peroxide levels in host leaves. We further found that the ArcZ regulon overlaps significantly with the regulons of transcription factors involved in oxidative sensing including Fnr and ArcA. In addition, we show that ArcZ regulates arcA at the post-transcriptional level suggesting a role for this system in mediating adaptations to oxidative state, especially during disease development.